1989
DOI: 10.1017/s0021859600084549
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between growth stage and digestible organic matter in triticale

Abstract: S U M M A R YIn two experiments the yield, digestibility, protein and cell wall contents of several autumn-sown triticale cultivars were compared with rye at defined growth stages. Yields at each growth stage were highest in the triticale cultivars. The content of leaf blade and sheath fell with increased maturity while stem and ear content increased. There were differences between cultivars in the contribution of individual stem internodes. Digestibility also declined with maturity for all plant parts, and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Mannerkorpi and Taube (1995) found that the highest nutritive value of barley was measured for the leaf sheath and blade in the uppermost internode and generally declined as senescence began. Brignall et al (1989) found for rye and triticale that percentage of the plant as leaf sheath and blade fell from jointing to anthesis, while stem and ear percentage increased. Hunt and Edgington (1981) found for winter wheat ( Triticum aestivum L.) that rapid spike growth commenced 2 wk after heading and continued to physiological maturity, while leaf weight declined during this period and stem weight increased to 3 wk after heading and then began to decline.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Mannerkorpi and Taube (1995) found that the highest nutritive value of barley was measured for the leaf sheath and blade in the uppermost internode and generally declined as senescence began. Brignall et al (1989) found for rye and triticale that percentage of the plant as leaf sheath and blade fell from jointing to anthesis, while stem and ear percentage increased. Hunt and Edgington (1981) found for winter wheat ( Triticum aestivum L.) that rapid spike growth commenced 2 wk after heading and continued to physiological maturity, while leaf weight declined during this period and stem weight increased to 3 wk after heading and then began to decline.…”
mentioning
confidence: 98%
“…As cereals mature from the vegetative through boot and dough stages, biomass increases (Cherney and Marten, 1982; Twidwell et al, 1987; Fearon et al, 1990; Bergen et al, 1991; Mislevy et al, 1997) and then declines as physiological maturity approaches (Hunt and Edgington, 1981; Baron and Kibite, 1987). During the time from vegetative to dough stage as stems elongate and secondary cell‐wall structures are laid down, whole‐plant quality declines (Cherney and Marten, 1982; Twidwell et al, 1987; Brignall et al, 1989; Fearon et al, 1990; Daccord and Arrigo, 1993; Hadjipanayiotou et al, 1996; Mislevy et al, 1997), as does the silage made from it (Acosta et al, 1991; Ben‐Ghedalia et al, 1995b). As the grain fills, quality, especially protein, may again improve as the grain makes up more and more of the total biomass (Ben‐Ghedalia et al, 1995a, 1995b; Mannerkorpi and Taube, 1995).…”
mentioning
confidence: 99%
“…Maturity of plants is a common denominator describing the decline in leaves relative to shoots even when interactions of environmental factors take place (Brignall et al, 1989;Marten, 1970;Deinum et al, 1981;Kilcher and Heinrichs, 1974). The decline in leaf growth relative to stem growth has been attributed to leaf loss and senescence (Kalu et al, 1990).…”
Section: Shoot and Leaf Drv Matter Distributionmentioning
confidence: 99%
“…Deinum et al (1981) reported that digestibility of organic matter declined faster at higher latitudes because stem development proceeded faster and because less leaf dry matter was produced. Thus, the leaf:stem ratio decreases with increase in latitude and because leaves have lower digestibility than stems, total herbage digestibility also declines (Brignall et al, 1989;Kalu et al, 1990;Marten, 1970). In contrast, Deinum et al (1981) reported that increased stem development at higher latitudes might not have much effect on digestibility because the more rapid development at northern latitudes does not have a negative effect on forage quality.…”
Section: Davlenothmentioning
confidence: 99%
See 1 more Smart Citation